PROBLEMS IN SOLVING SIMPLE PROBLEMS IN MATHEMATICS IN PRIMARY SCHOOLS - Zaxiya Akhmedovna Narimbetova; Zilfira Dineeva (Bright Mind Publishing, 2025)
This article outlines the main methods for solving logical problems, the teaching methodology is studied, and some of the general issues of the methodology for teaching problem solving are analyzed.
Keywords: Method, order, logical problems, analysis, error, technique, logic, component, motivation, activity.